Renewable Energy Consumption-Growth Nexus in European Countries: A Sectoral Approach. (April 2023) - Simionescu, Mihaela; Rădulescu, Magdalena; Cifuentes-Faura, Javier
The renewable energy consumption plays a significant role in achieving sustainable development, but a sectoral approach is necessary to design the better recommendations for each sector. In this context, the main objective of this paper is to assess the impact of the use of this type of energy on economic growth in 23 European Union (EU) member states in the period 1990–2020. Besides overall renewable energy consumption, different utilisations of this energy are considered: in industry, transport, in commercial and public services, and for residential purposes. The methodological background is built around panel data models that start from a Cobb–Douglas function. The renewable energy consumption is considered an important factor that should generate economic growth. The panel data approach based on causality analysis and Augmented Mean Group and Common Correlated Effects Mean Group estimators suggests that renewable energy use in industry does not determine economic growth, but economic development is a cause for more utilisation of this energy in industry. In addition, more renewable energy consumption in transport enhances economic growth. A high level of economic development can promote the consumption of renewable energies in industrial sectors. In this way, industrial companies can allocate more financial funds to research in the field of renewable energies and can afford to adopt renewable energy sources. Investment in biofuels can contribute to achieving sustainable transport in the EU.